2006
DOI: 10.1212/01.wnl.0000238511.72927.3c
|View full text |Cite
|
Sign up to set email alerts
|

Association of aortic plaque with intracranial atherosclerosis in patients with stroke

Abstract: The presence of simple aortic plaques may be a marker of advanced vascular disease. Detection of simple aortic plaques during transesophageal echocardiography may have clinical implications because patients with these plaques frequently had concomitant intracranial atherosclerosis, a risk factor for stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 15 publications
1
31
0
1
Order By: Relevance
“…Briefly, age may be reflective of duration of exposure to vascular risk factors on plaque formation, whereas the negative association of small-vessel occlusive strokes and AA atheroma progression probably reflects a converse positive association between the non-small-vessel occlusive strokes (cardioembolism and large-artery atherothrombosis) and AA atheroma progression. Prior studies have reported an association of large-artery atherothrombois 32 and cardioembolic sources 33 with AA atheroma. Finally, complex mobile plaques are thought to represent mobile "debris" or a free-floating thrombus that might serve as a nidus for plaque activity and progression by thrombus accretion.…”
Section: Discussionmentioning
confidence: 94%
“…Briefly, age may be reflective of duration of exposure to vascular risk factors on plaque formation, whereas the negative association of small-vessel occlusive strokes and AA atheroma progression probably reflects a converse positive association between the non-small-vessel occlusive strokes (cardioembolism and large-artery atherothrombosis) and AA atheroma progression. Prior studies have reported an association of large-artery atherothrombois 32 and cardioembolic sources 33 with AA atheroma. Finally, complex mobile plaques are thought to represent mobile "debris" or a free-floating thrombus that might serve as a nidus for plaque activity and progression by thrombus accretion.…”
Section: Discussionmentioning
confidence: 94%
“…Aortic atheromatous plaques are more frequently found in elders, smokers, and in patients with hypertension, diabetes mellitus, or hypercholesterolemia. 3 The presence of plaques in the aorta was found to be significantly associated with both intracranial and extracranial atherosclerosis in patients with stroke, 24 whereas plaques in the arch and descending aorta were found to be an independent predictor of >70% extracranial carotid artery stenosis in patients with stroke or transient ischemic attack. 25 Age, smoking history, and pulse pressure were independently associated with a higher frequency of atherosclerosis and complex atherosclerosis in the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of coronary atherosclerosis in Korean patients, however, may be stronger for extracranial carotid atherosclerosis than LAICOD. 18 Concomitant occurrence of LAICOD and coronary atherosclerosis should not be unexpected because intracranial atherostenosis may be associated with aortic plaque 19 and metabolic syndrome, 20 factors that may be associated with coronary atherosclerosis. The GESICA natural history study based in France suggests both a high 2-year recurrence rate of ischemic events in the stenotic cerebral artery territory (38.2% with stroke accounting for 13.7% and transient ischemic attack 24.5% of events) and cardiovascular events in 18.6% with an 8.8% vascular death rate.…”
Section: Risk Of Stroke and Other Cardiovascular Disease In Large Artmentioning
confidence: 99%